PENDIDIKAN BERBASIS KETERAMPILAN ABAD 21 UNTUK MENJAWAB TANTANGAN PEMBANGUNAN - Mariah Siskawati; Johanna Pratiwi Suyono; Agus Tinus (CV. Lafadz Jaya, 2026)
This study on 21st-century skills-based education highlights the importance of critical thinking, creativity, communication, and collaboration (4C), digital literacy, and adaptive character in responding to increasingly complex development challenges. In the context of national development and the sustainable development agenda, education can no longer focus solely on rote learning but must equip learners with the ability to solve real-world problems in society and the workplace. This article examines the concept of 21st-century skills, the challenges of their implementation in educational institutions, and their relevance to sustainable development needs. The method used is a literature study of education policies, global competency frameworks, and various innovative learning practices oriented toward 4C and new literacies. The findings show that strengthening project-based learning, utilizing digital technology, and integrating local–global development issues into the curriculum can enhance the relevance of education to development needs. However, the success of implementation greatly depends on teacher capacity, infrastructure support, and consistent policies that position 21st-century skills as key indicators of education quality. These findings underscore the urgency of systemic educational transformation to produce human resources who are excellent, competitive, and able to contribute meaningfully to sustainable development.